The nature of Supreme Court power - Hall, Matthew Eric Kane (New York Cambridge University Press, 2011)
"This book offers a comprehensive theory of Supreme Court power, identifying conditions under which the Court is successful at altering the behavior of state and private actors. Matthew E. K. Hall depicts the Court as a powerful institution, capable of exerting significant influence over social change"-- Provided by publisher.
Keywords: United States. -- Supreme Court -- History; Political questions and judicial power -- History -- United States -- Sources; Judgments -- History. -- United States; Constitutional history -- United States; United States -- Social conditions -- Sources